PENGARUH KEPEMIMPINAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KEPUASAN KERJA, MOTIVASI KERJA, DAN KINERJA KARYAWAN BANK SULSELBAR - Agung Widhi Kurniawan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2012)
This study aims to explain the effect of leadership and human resource development on job satisfaction, job motivation and employees performance. Analysis by using Structural Equation Modeling (SEM) with alpha 5% to test the significance of research variable. The data were taken from all Bank Sulselbar employees using cluster random sampling technique. The total respondents were 184 respondents. Questionnaire (main instrument), interview, observation, and documentary were used in collecting the data. Results of analysis (at significance level of 5%) showed that: 1) leadership has a significant effect on job satisfaction, 2) human resource development has a significant effect on job satisfaction, 3) leadership has a significant effect on job motivation, 4) human resource development has a significant effect on job motivation, 5) leadership has a significant effect on employee performance, 6) human resource development has a significant influence employee performance, 7) job satisfaction has a significant effect on job motivation, 8) job satisfaction has a significant effect on employee performance, and 9) job motivation does not significantly affect on employee performance.